2007
DOI: 10.1002/ijc.22549
|View full text |Cite
|
Sign up to set email alerts
|

Dietary isothiocyanates, GSTM1, GSTT1, NAT2 polymorphisms and bladder cancer risk

Abstract: TXIsothiocyanates (ITCs) are nonnutrient compounds in cruciferous vegetables with anticarcinogenic properties. ITCs down-regulate cytochrome P-450 biotransformation enzyme levels, activate Phase II detoxifying enzymes and induce apoptosis. On the other hand, ITCs also serve as a substrate for GSTs. Experimental evidences suggest that ITCs have anticarcinogenic effect on bladder cancer. Therefore, we evaluated dietary intake of ITCs, GSTM1, GSTT1 and NAT2 polymorphisms, and bladder cancer risk in a case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 34 publications
2
53
1
2
Order By: Relevance
“…DNA was isolated from peripheral blood lymphocytes by standard SDS/ proteinase K method. Genotyping procedures for GSTM1 and NAT2 were described previously (32). In our laboratory, strict quality control procedures for genotyping are implemented to ensure high genotyping accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was isolated from peripheral blood lymphocytes by standard SDS/ proteinase K method. Genotyping procedures for GSTM1 and NAT2 were described previously (32). In our laboratory, strict quality control procedures for genotyping are implemented to ensure high genotyping accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary fiber is known to alter the coronary environment in such a way as to protect against colorectal diseases (Ekumankama 2008). It provides protection by increasing fecal bulk, which dilutes the increased colonic bile that occurs with high fat diet (Dillard and German 2000;Zhao et al 2007). When found in excess, it may bind some essential trace elements leading to deficiency of some minerals such as iron and zinc (Ekwumemgbo et al 2014).…”
Section: Proximate Compositionmentioning
confidence: 99%
“…Recently, Zhao et al (40) estimated the amount of dietary isothiocyanates consumed in a study in Singapore based on food frequency questionnaires, and found that high isothiocyanate intake was inversely associated with bladder cancer risk (OR, 0.71; 95% CI, 0.57-0.89). Furthermore, this association between the intake of isothiocyanates and bladder cancer risk was more evident in ever smokers and heavy smokers in stratified analyses, which is consistent with our findings.…”
Section: Cancer Epidemiology Biomarkers and Prevention Cancer Epidemiomentioning
confidence: 99%